Kolaborasi Pembangunan Desa Berkelanjutan Melalui Program Dana Desa Di Kecamatan Sokaraja Kabupaten Banyumas - Andi Antono; Mahmud Setiahadi; Ngalimun Ngalimun (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2020)
Village funds which have become a pendulum for village development provide quite a formidable task for village village administrators to make the best use of them. The involvement of public and community actors at the local level is a strategic step in managing village funds to provide a transparent and accountable effect, as mandated by the collaborative governance model so that the results of development become more beneficial for the citizens. This research uses a qualitative method. The technique of taking informants is done by snowball sampling while maintaining independence in expressing opinions. Data collection methods with in-depth interviews, observation and document analysis. Data analysis was carried out interactively, starting from data collection, data condensation, data appearance, and research conclusions drawn and combined with the appearance of descriptive data. The results showed that the collaborative process had proceeded well as seen from face-to-face dialogue, building trust, community commitment and various understandings of the development had an impact on effective development outcomes both physical and non-physical in nature.